GREEN BUSINESS UMKM DI KOTA DEPOK - Hartono .; Anita Maulina; Noviandari .; Sukirno .; Muhammad Sholeh (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
Depok is the smallest in west Java with such problems as garbage that pollutes several large rivers such as ciliwung and cisadane trash from small industries and communities, which can be reduced by umkm as the donor of 65% of the regional product.Public service activities for umkm city depok endeavor to help umkm's doers to be more conscious of the environment by adopting green business.It is known that most of the people involved in the depok city have low environmental awareness. Socializing can open up the insights of umkm doers to applyGreen business is his small business. By implementing green business, umkm perpetrators can alsoSaves operating costs or production costs even promotional costs.The reuse of reusable containers or the use of banana leaves in place of plastic containers adds to the traditional and unique value and to the culinary siri typical of depok cuisine. Such community service is to be expected to be an activity capable of carrying the city of depok as a friendly city or